1965
DOI: 10.1097/00006842-196503000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Body Perception and Symptom Localization

Abstract: The hypothesis was tested that individuals whose body-awareness pattern concentrates more on the exterior than the interior experience relatively more exterior than interior symptoms when ill. One hundred healthy young college students were used as subjects. The hypothesis was tested by correlating a Rorschach measure of differential body awareness obtained by utilizing the barrier (Fisher and Cleveland) minus the body-interior (Cassell) score with a subject's symptom pattern. The latter was obtained by use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…3261 Accordingly, 527 unlike a Prosecutor, a victim who is just dissatisfied with the length of an imprisonment sentence against the convicted cannot seek mandamus review. 3262 Nevertheless, the victim is entitled to appeal a Judge's restitution decision since an erroneous restitution decision deprives a victim of 'the right to full and timely restitution as provided in law'. 3263 Concerning restitution, the Sixth Federal Circuit Court of Appeals in United States v. Perry rejected previous case law and instead permitted a crime victim to appeal a District Court releasing a lien in favor of victim securing a restitution.…”
Section: American Adversarial Systemmentioning
confidence: 99%
“…3261 Accordingly, 527 unlike a Prosecutor, a victim who is just dissatisfied with the length of an imprisonment sentence against the convicted cannot seek mandamus review. 3262 Nevertheless, the victim is entitled to appeal a Judge's restitution decision since an erroneous restitution decision deprives a victim of 'the right to full and timely restitution as provided in law'. 3263 Concerning restitution, the Sixth Federal Circuit Court of Appeals in United States v. Perry rejected previous case law and instead permitted a crime victim to appeal a District Court releasing a lien in favor of victim securing a restitution.…”
Section: American Adversarial Systemmentioning
confidence: 99%
“…This was proposed partly to substantiate the first hypothesis by demonstrating that high barrier subjects did not have a generalized facility in tachistoscopic recognition of body themes. T h e second comparison was to be made by deriving for each subject a score based upon his barrier minus body interior awareness index (Cassell, 1965). In this regard the experimental design proposed to classify subjects as having accentuated internal awareness on the basis of low barrier minus body interior awareness scores.…”
Section: Wilfred a Cassellmentioning
confidence: 99%
“…Thus, individuals most attentive to the protective or boundary characteristics of inkblot stimuli ("high barrier" individuals) have been found to be more subject to symptoms with a body-exterior than with a body-interior locus-eg, symptoms of arthritis 2 or of itching and generalized muscle pain. 3 Other experiments 4 ' s have demonstrated that body experiences intrude into a wide variety of cognitive and perceptual processes.…”
mentioning
confidence: 99%